2007
DOI: 10.1002/rcm.3129
|View full text |Cite
|
Sign up to set email alerts
|

‘LC‐electrolyte effects’ improve the bioanalytical performance of liquid chromatography/tandem mass spectrometric assays in supporting pharmacokinetic study for drug discovery

Abstract: The development of rapid and sensitive bioanalytical methods in a short time frame with acceptable levels of precision and accuracy is imperative for successful drug discovery. We previously reported that the use of a mobile phase containing an extremely low concentration of ammonium formate or formic acid increased analyte electrospray ionization (ESI) response and controlled against matrix effects. We designated these favorable effects 'LC-electrolyte effects'. In order to support rapid pharmacokinetic (PK) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 30 publications
1
14
1
Order By: Relevance
“…It represents a combination of analyte charging, droplet evaporation, and ion transmission efficiencies in the vacuum system. The results from our current and earlier studies [4,6,7] indicate that the electrolyte modification of mobile phase can significantly improve the ESI efficiency, resulting in enhanced analyte responses. For quantification purposes, the magnitude of ionization efficiency should be maintained constantly throughout an analyte concentration range; the ability to hold the ionization efficiency is called the "ionization capacity".…”
Section: Reduction Of Matrix Effects and Chromatographic Run Timesupporting
confidence: 53%
See 1 more Smart Citation
“…It represents a combination of analyte charging, droplet evaporation, and ion transmission efficiencies in the vacuum system. The results from our current and earlier studies [4,6,7] indicate that the electrolyte modification of mobile phase can significantly improve the ESI efficiency, resulting in enhanced analyte responses. For quantification purposes, the magnitude of ionization efficiency should be maintained constantly throughout an analyte concentration range; the ability to hold the ionization efficiency is called the "ionization capacity".…”
Section: Reduction Of Matrix Effects and Chromatographic Run Timesupporting
confidence: 53%
“…ESI signal intensity of a given analyte is a function of the percentage of electrolytic content in mobile phase [6,7]. We found that the highest ESI response was achieved for all analytes when the mobile phase included 0.2 mM HCOONH 4 .…”
Section: Sensitive Esi-ms/ms Of All the Ginkgo Analytesmentioning
confidence: 83%
“…The mobile phase, which consisted of solvent A (water/acetonitrile, 98:2, v/v, containing 1 mM formic acid) and solvent B (water/acetonitrile, 2:98, v/v, containing 1 mM formic acid), was delivered at 0.35 ml/min, except for in the analysis of creatinine at 0.7 ml/min. A pulse gradient elution method was used in the measurement of the compounds (except for creatinine), with an analytedependent start proportion (0-50% solvent B) and analyte-independent elution proportion (100% solvent B), elution proportion segment (1.5 minutes), and column equilibrium segment (3.5 minutes) (Wang et al, 2007); for creatinine, the gradient parameters were 100% solvent B and 80% solvent B, 1 minute and 7 minutes, respectively. …”
Section: Methodsmentioning
confidence: 99%
“…The LC separation was achieved on a Synergi 5 m C18 column (Phenomenex, Torrance, CA). The LC mobile phases were CH 3 OH/H 2 O (2:98, v/v, containing 0.08 mM HCOONH 4 ) for A and CH 3 OH/H 2 O (98:2, v/v, containing 0.08 mM HCOONH 4 ) for B, which were used for pulse gradient chromatography (Wang et al, 2007). The gradient parameters including the start proportion, the elution proportion, the elution proportion segment, and the column equilibrium segment were 15% B, 100% B, 5.4, and 4.4 min, respectively, except for excretory samples requiring a 5-min start proportion segment.…”
Section: Methodsmentioning
confidence: 99%